Making budgets : public resource allocation - Danziger, James N.; Golembiewski, Robert T. (Beverly Hills : Sage Publications, 1978)
The author focused his comparative design on British county boroughs ,an all-purpose local authority in English and Welsh urban communities, and searched for similarities /differences in the yearly revenue budget
Includes index.
Includes bibliographical references: p. 243-249.
obn22/01/2019
Loans
Keywords: Local budgets